2017
DOI: 10.1371/journal.pone.0181227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of statistical methods for early temporal detection of outbreaks: A simulation-based study

Abstract: The objective of this paper is to evaluate a panel of statistical algorithms for temporal outbreak detection. Based on a large dataset of simulated weekly surveillance time series, we performed a systematic assessment of 21 statistical algorithms, 19 implemented in the R package and two other methods. We estimated false positive rate (FPR), probability of detection (POD), probability of detection during the first week, sensitivity, specificity, negative and positive predictive values and F1-measure for each d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 39 publications
1
53
0
Order By: Relevance
“…In their study, the CUSUM method with adaptive regression residuals showed better results than EARS. Recently, Gabriel et al [ 11 ] compared 21 statistical algorithms for temporal outbreak detection. However, these studies did not include time series forecasting methods.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, the CUSUM method with adaptive regression residuals showed better results than EARS. Recently, Gabriel et al [ 11 ] compared 21 statistical algorithms for temporal outbreak detection. However, these studies did not include time series forecasting methods.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, regression models like Farrington do not perform well for small outbreaks (low number of patients) like those in our hospital and in most other hospital settings [25]. Previously it was shown in a simulation study that Farrington has a low sensitivity [26]. Therefore, it is possible that the Farrington algorithm alone should not be the algorithm of choice for regular hospital outbreaks.…”
Section: Outbreaks Of Endemic Pathogensmentioning
confidence: 75%
“…As a result of an increase in the amount of K, the probability of generation alarm on the first day of outbreaks decreased due to an increase in the level of alarm thresholds. The median, minimum and maximum timeliness (according to day) in Haar (k; 0.5) and db10 (k: 0.5) wavelets based method was 2 (1 to 14) and 2 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) respectively. This amount was less than the median timeliness of other algorithms.…”
Section: Timeliness Of Methodsmentioning
confidence: 99%
“…collection, analysis, interpretation and final dissemination in public health practice. No doubt, the surveillance system will contribute to reducing the morbidity and mortality due to health-related events (3). Additionally, utilizing a suitable method in a surveillance system for early detection of naturally occurring or bioterrorism-related outbreaks have a very important role in reducing the time between outbreak occurrence and detection (4).…”
mentioning
confidence: 99%